Methylglyoxal Causes Dysfunction of Thioredoxin and Thioredoxin Reductase in Endothelial Cells - Ryosuke Tatsunami; Tatsuya Oba; Kyohei Takahashi; Yoshiko Tampo (Elsevier, 2009)
Methylglyoxal (MG), a reactive dicarbonyl produced during glucose metabolism, induces oxidative stress and apoptosis. Under hyperglycemic conditions, the abnormal accumulation of MG is related to the development of diabetic complications. We examined the effects of MG on thioredoxin (Trx) and glutaredoxin (Grx) systems, two thiol-disulfide oxidoreductase systems that protect against oxidative damage of proteins, in bovine aortic endothelial cells (BAECs). The levels of protein carbonyls as markers of protein oxidation increased in BAECs exposed to MG at 5 mM, resulting in the loss of cell viability. Western blot analysis demonstrated that Trx protein level decreased when BAECs were exposed to 5 mM MG. MG also inactivated Trx reductase, which maintains Trx in the reduced/active state. Moreover, peroxiredoxin, which is dependent on Trx and Trx reductase to maintain its reduced state, was oxidized by 5 mM MG. No significant difference in the levels of Trx, Trx reductase, or peroxiredoxin was observed in BAECs exposed to MG at 1 mM; this concentration had little effect on protein carbonyl formation and cell viability. MG failed to decrease Grx activity, indicating that Trx is more susceptible to MG than Grx. Taken together, these findings suggest that MG causes dysfunction of the Trx system, including Trx and Trx reductase, in BAECs. Keywords:: methylglyoxal, thioredoxin, thioredoxin reductase, peroxiredoxin, endothelial cell